Dual function of clock component OsLHY sets critical day length for photoperiodic flowering in rice. Issue 8 (5th May 2021) - Sun, Changhui; Zhang, Kuan; Zhou, Yi; Xiang, Lin; He, Changcai; Zhong, Chao; Li, Ke; Wang, Qiuxia; Yang, Chuanpeng; Wang, Qian; Chen, Congping; Chen, Dan; et al.
Summary: Circadian clock, an endogenous time‐setting mechanism, allows plants to adapt to unstable photoperiod conditions and induces flowering with proper timing. In Arabidopsis, the central clock oscillator was formed by a series of interlocked transcriptional feedback loops, but little is known in rice so far. By MutMap technique, we identified the candidate gene OsLHY from a later flowering mutant lem1 and further confirmed it through genetic complementation, RNA interference knockdown, and CRISPR/Cas9‐knockout. Global transcriptome profiling and expression analyses revealed that OsLHY might be a vital circadian rhythm component. Interestingly, oslhy flowered later under ≥12 h day length but headed earlier under ≤11 h day length. qRT‐PCR results exhibited that OsLHY might function through OsGI ‐ Hd1 pathway. Subsequent one‐hybrid assays in yeast, DNA affinity purification qPCR, and electrophoretic mobility shift assays confirmed OsLHY could directly bind to the CBS element in OsGI promoter. Moreover, the critical day length (CDL) for function reversal of OsLHY in oslhy (11–12 h) was prolonged in the double mutant oslhy osgi (about 13.5 h), indicating that the CDL set by OsLHY was OsGI dependent. Additionally, the dual function of OsLHY entirely relied on Hd1, as the double mutant oslhy hd1 showed the same heading date with hd1 under about 11.5, 13.5, and 14 h day lengths. Together, OsLHY could fine‐tune the CDL by directly regulating OsGI, and Hd1 acts as the final effector of CDL downstream of OsLHY . Our study illustrates a new regulatory mechanism between the circadian clock and photoperiodic flowering.